Digital Economy And Economic Growth: The Role Of E-Commerce In Developing Countries - Claudyus Defri Telaumbanua; Aris Niat Wati Hulu (Journal of Global Economic Development and Policy, 2026)
The rapid development of the digital economy has significantly transformed economic structures, particularly in developing countries. This study aims to examine the role of e-commerce in driving economic growth by analyzing its impact on key macroeconomic indicators. Using a quantitative approach with panel data from developing countries over the period 2015–2023, this research applies econometric techniques, including the Fixed Effects Model (FEM), to assess the relationship between e-commerce adoption and economic growth. The findings reveal that e-commerce has a positive and statistically significant effect on GDP growth, supported by factors such as internet penetration, human capital, foreign direct investment, and infrastructure development. However, the study also identifies several challenges, including the digital divide, limited digital literacy, and inadequate regulatory frameworks, which hinder the optimal utilization of e-commerce in some countries. The results suggest that while e-commerce serves as a key driver of economic development, its effectiveness depends on the presence of supportive ecosystems and policies. Therefore, governments in developing countries should prioritize digital infrastructure investment and policy reforms to maximize the benefits of the digital economy. This study contributes to the growing literature on digital transformation and provides policy-relevant insights for fostering inclusive and sustainable economic growth.